Det universitets- og høgskolepedagogiske vitenskapsområdet i Norge - Husebø, Dag; Ferguson, Leila; Isaksen, Robert; Aarø Engen, Dagrun Astrid; Hofgaard Lycke, Kirsten; Strømsø, Helge I.; Wittek, Line; Hagen, Randi Elisabeth; Huatorpet, Siw; Lefdal, Hans Erik; Nordkvelle, Yngve; Fossland, Trine; et al. (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2025)
The book provides an insight into the fields of teaching and research in higher education in Norway today. Furthermore, the history and development of the scientific area, and central characteristics of the work university and college pedagogues (University pedagogues) carry out are presented. In this way, the book constitutes an updated knowledge base for higher education (HE) pedagogy in the Norwegian context. The book's chapters are individual scientific and peer-reviewed chapters that can be read individually based on a specific area of interest. While the book's chapters each represent a unique contribution, the book can and should also be read as a whole, where the different parts touch and elaborate on various overarching themes.